2017
DOI: 10.1039/c7dt02001e
|View full text |Cite
|
Sign up to set email alerts
|

Organic-free synthesis of zincoaluminosilicate zeolites from homogeneous gels prepared by a co-precipitation method

Abstract: Zeolites containing Zn in their frameworks are promising materials for ion-exchange and catalysis because of their unique ion-exchange capabilities and characteristic Lewis acidity. However, expensive organic compounds often required in their synthesis can prevent their practical uses. Here, a facile organic-free synthesis route for new zincoaluminosilicate zeolites having MOR topology, in which both Zn and Al are substituted in the framework, is demonstrated for the first time. The use of homogeneous zincoalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For the synthesis of zeolite‐like materials with Zn in the frameworks, the formation of the homogeneous mixture of Zn and Si species is crucial to form the zincosilicate structures while preventing the precipitation of zinc oxides/hydroxides during hydrothermal treatment . In procedure (i), Zn species are totally dissolved as [Zn(OH) 4 ] 2− or [Zn(OH) 3 ] − in the clear solution because of the high alkalinity of TMAdaOH solution (pH >14) .…”
Section: Figurementioning
confidence: 82%
See 3 more Smart Citations
“…For the synthesis of zeolite‐like materials with Zn in the frameworks, the formation of the homogeneous mixture of Zn and Si species is crucial to form the zincosilicate structures while preventing the precipitation of zinc oxides/hydroxides during hydrothermal treatment . In procedure (i), Zn species are totally dissolved as [Zn(OH) 4 ] 2− or [Zn(OH) 3 ] − in the clear solution because of the high alkalinity of TMAdaOH solution (pH >14) .…”
Section: Figurementioning
confidence: 82%
“…As reported recently, zincosilicate zeolite‐like materials show strong Lewis acidity . FTIR analysis of Zn‐CHA2, after adsorption of deuterated acetonitrile (CD 3 CN) at 80 °C and then desorption at 80–250 °C, was performed to characterize its Lewis acid sites in comparison with zincoaluminosilicate CHA (Zn,Al‐CHA; Si/Al=10.5, Si/Zn=15.3) (see Figures S8 and S9, and Table S1 in the Supporting Information).…”
Section: Figurementioning
confidence: 96%
See 2 more Smart Citations
“…Constructing a support–metal–strong-interaction (SMSI) catalyst is a general guide with various top-down and down-top methods. Incorporation of metal ions or oxides into the framework or the matrix of supports can be realized under a one-pot synthesis condition, where the precursors of the metal and the elements of the support (such as Si and Al) are placed together in a beaker or autoclave. For example, Yang et al reported an Fe-containing MFI siliceous zeolite and Bian synthesized a mesoporous-silica-stabilized Co- m SiO 2 catalyst, and these catalysts have −M δ+ –O δ− – structures that are not easily reduced and have been demonstrated to be active, selective, and stable for alkane dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%